Recent Trends in Niosome as Vesicular DrugDelivery System - Anchal Sankhyan, Pravin Pawar (Journal of Applied Pharmaceutical Science)
Over decades researchers are striving to use the drugs in an efficient manner to treat various diseases. The efficient use can be explained as reduced dose, reduced side effects, reduced dosage frequency, greater patient compliance and maximum concentration of the drug at the site of action so as to reduce the undue exposure to the entire body. The article focuses on various advantages of vesicular systems (niosomes) to develop the effective delivery system to achieve maximum effective concentration. Niosomes, nonionic surfactant vesicles with lamellar structure which may be unilamellar and multilamellar serve to be efficient in providing these required advantages. The bilayer structure of niosomes being amphiphillic in nature can be used to deliver hydrophilic drugs in its aqueous core and lipophilic drugs in the bilayer made up of surfactants. Various additives in niosomes include nonionic surfactant as film forming agent, cholesterol as stabilizing and rigidizing agent for the bilayer and various charge inducers which develop a charge on the surface of niosomes and stabilize the prepared formulation by the resulting repulsive forces. This article also comprises of various breakthroughs in niosomal delivery of drugs representing various classes. On the basis of above information, the niosomes have been thoroughly exploited for the drug delivery system and still offer scope for research on various drugs for their maximum therapeutic utilization in management and treatment of various dreadful diseases.
Keywords: Vesicular system,niosomes,nonionic surfactant,cholesterol.